Hubungan Pola Asuh Dengan Kejadian Stunting Pada Balita Usia 24-59 Bulan Di Wilayah Pesisir Kelurahan Mandala Kota Jayapura - Adimuntja, Natalia Paskawati; Mamoribo, Sherly Novita (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
Stunting is a condition of failure to thrive in children under the age of five due to chronic malnutrition and recurrent infections, especially in the First 1,000 Days of Life (1). The prevalence of stunting in 2022 in Jayapura City was 20.6% (2). Data on stunted toddlers in Mandala Village were 67 toddlers in 2021, 132 toddlers in 2022 and 121 toddlers in January to September 2023 (3). The purpose of the study was to determine the relationship between parenting patterns and the incidence of stunting in toddlers aged 24-59 months in the coastal area of Mandala Village, Jayapura City. The type of research is an analytical observational study with a cross-sectional design. The study was conducted in Mandala Village, Jayapura City. The study population was all toddlers aged 24-59 months in Mandala Village, Jayapura City with a sample size of 100 respondents. The sampling technique was purposive sampling. Interviews were conducted using a questionnaire. Data analysis was univariate and bivariate analysis using the chi-square statistical test. The results of the study showed that there were 14 toddlers with stunting (14.0%) and 86 toddlers without stunting (86.0%). The results of the bivariate analysis showed that parenting patterns based on psychosocial stimulation (p-value = 0.009) were significantly related to the incidence of stunting in toddlers in the Coastal Area of Mandala Village, Jayapura City. Meanwhile, the use of health services (p-value = 0.460) was not significantly related to the incidence of stunting in toddlers in the Coastal Area of Mandala Village, Jayapura City. It is recommended that mothers of toddlers can improve their understanding and skills, in order to optimize the provision of stimulation to their toddlers, either in physical, verbal or auditory forms.